2018
DOI: 10.1159/000490492
|View full text |Cite
|
Sign up to set email alerts
|

Executive Impairments in Binge Drinking: Evidence for a Specific Performance-Monitoring Difficulty during Alcohol-Related Processing

Abstract: This study evaluated inhibition and performance-monitoring abilities through the explicit processing of alcohol cues. Twenty-two binge drinkers (BD) and 22 control participants performed a speeded Go/No-Go task using pictures of alcohol and soft cans as Go and No-Go targets. This task measures inhibitory control and performance monitoring (i.e., task adjustment through errors and feedback processing) during the explicit processing of alcohol cues. Groups did not significantly differ regarding inhibition abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 55 publications
(80 reference statements)
1
11
0
1
Order By: Relevance
“…Third, some studies indicated that the relationship between binge drinking and inhibition was instead characterized by impairments in performance monitoring, in particular difficulty in adjusting one’s behavioral response following commission errors (Bø et al, 2016a). This proposal was confirmed by using behavioral and electrophysiological measures in case-control studies involving binge drinkers and control participants (Lannoy et al, 2017b; Lannoy et al, 2018a; Smith & Mattick 2013). These inconsistencies between studies were addressed in a recent systematic review of the neuropsychological studies in binge drinking; the authors concluded, after careful consideration of the literature, that binge drinkers are indeed characterized by inhibition impairments (Carbia et al, 2018b).…”
Section: Literature Reviewmentioning
confidence: 75%
See 1 more Smart Citation
“…Third, some studies indicated that the relationship between binge drinking and inhibition was instead characterized by impairments in performance monitoring, in particular difficulty in adjusting one’s behavioral response following commission errors (Bø et al, 2016a). This proposal was confirmed by using behavioral and electrophysiological measures in case-control studies involving binge drinkers and control participants (Lannoy et al, 2017b; Lannoy et al, 2018a; Smith & Mattick 2013). These inconsistencies between studies were addressed in a recent systematic review of the neuropsychological studies in binge drinking; the authors concluded, after careful consideration of the literature, that binge drinkers are indeed characterized by inhibition impairments (Carbia et al, 2018b).…”
Section: Literature Reviewmentioning
confidence: 75%
“…Performance monitoring difficulties but no global inhibition alterations (Bø et al, 2016a; Lannoy et al, 2017b; Lannoy et al, 2018a; Smith & Mattick, 2013).…”
Section: Questions and Perspectives For Future Researchmentioning
confidence: 99%
“…Likewise, Rose and Grunsell (2008) found weak group-effects in a delay discounting task and no difference between binge drinkers and controls in a time estimation task. Lannoy, Maurage, D'Hondt, Billieux, and Dormal (2018) found no difference regarding inhibition abilities in a speeded Go/No-Go task between binge drinker and control participants.…”
Section: Introductionmentioning
confidence: 61%
“…In a study of Bø et al (2016) the binge score could not predict inhibition performance in a stop signal-task, but an impairment in response adjustment after errors in this task. Rose and Grunsell (2008) and Lannoy et al (2018) also found no association of binge drinking with impulsivity task performance. Using the Iowa Gambling Task (IGT) Goudriaan et al (2007) only found deficits in decision making in heavy binge drinkers.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation